Theoretical Foundations for Improving the Mechanisms of Attracting Innovations in Tourism Service Development: Landasan Teoritis untuk Meningkatkan Mekanisme Penarikan Inovasi dalam Pengembangan Layanan Pariwisata - Shokirov Firdavs (Academia Open, 2025)
General Background: Tourism is a pivotal sector in Uzbekistan’s economic transformation, increasingly influenced by technological and structural shifts. Specific Background: Despite strategic policy efforts, empirical studies examining how innovation mechanisms shape tourism services in transitioning economies remain limited. Knowledge Gap: Prior research lacks integrated analyses of multidimensional innovation effects on tourism performance in post-Soviet and Central Asian contexts. Aim: This study investigates the impact of five innovation dimensions—digital innovation adoption, smart tourism infrastructure, cluster participation, financial access, and government support—on tourism service development in Uzbekistan from 2022 to 2024. Results: Using firm- and region-level data and a multivariate regression model, all five innovation variables significantly and positively influenced service development, as measured by tourist arrivals, satisfaction, and revenue. Digital innovation and infrastructure had the strongest effects. Novelty: The study provides a comprehensive empirical model grounded in innovation diffusion theory and tourism-specific frameworks, offering the first integrated assessment of innovation drivers in Uzbekistan’s tourism sector. Implications: The findings emphasize the need for cohesive innovation policies, digital capacity-building, and targeted financial instruments to sustain tourism growth. Policymakers should foster public-private synergies to transition towards a technology-driven, competitive tourism economy. Highlights: Digital innovation significantly boosts tourism growth and visitor satisfaction. Financial access and policy support enable service modernization. First empirical model on tourism innovation in Uzbekistan. Keywords: Tourism Innovation, Digital Transformation, Smart Infrastructure, Policy Support, Uzbekistan